Comparison between self-reported sleep duration and actigraphy among adolescents: gender differences - Luciane Gaspar Guedes; Gabriela de Azevedo Abreu; Daniel Frossard Rodrigues; Liliane Reis Teixeira; Ronir Raggio Luiz; Katia Vergetti Bloch
ABSTRACT: Introduction: There are only few agreement studies between subjective measures of sleep and actigraphy among adolescents. Objective: To compare self-reported sleep and actigraphy in this age group, by studying gender differences and, using a new graphical approach, the survival agreement plot. Methods: Thirty-seven subjects, aged 12 to 17 years, answered questions about nocturnal sleep duration and used actigraphy for seven days. The mean and median differences between the informed sleep and the recorded one, the intraclass correlation coefficient, the Bland-Altman plot and the survival-agreement plot were used. Results: A mean difference of about one hour (SD = 2.1; median = 0.5; p < 0.01) was found between both strategies, which was higher among boys, 1.9 hours (SD = 2.8; median = 1.6; p < 0.05), than among girls, 0.5 hours (SD = 1.4; median = 0.3; p = 0.11). The graphical evaluation showed similar results, as well as the intraclass correlation coefficient: 0.06 (95%CI = -0.33 - 0.46; p = 0.489) for boys and 0.43 (95%CI = 0.12 - 0.83; p < 0.001) for girls. Conclusions: Our data are consistent with previous studies as to non-agreement between the two methods. These results are relevant because this is the first study of concordance between subjective measures of sleep and actigraphy among Brazilian adolescents, as far as we know. In addition, they reinforce the need of a careful use of nocturnal sleep measures among adolescents, mainly among boys.